2001
DOI: 10.1074/jbc.m105796200
|View full text |Cite
|
Sign up to set email alerts
|

Gleevec (STI571) Influences Metabolic Enzyme Activities and Glucose Carbon Flow toward Nucleic Acid and Fatty Acid Synthesis in Myeloid Tumor Cells

Abstract: Chronic myeloid leukemia cells contain a constitutively active Bcr-Abl tyrosine kinase, the target protein of Gleevec (STI571) phenylaminopyrimidine class protein kinase inhibitor. Here we provide evidence for metabolic phenotypic changes in cultured K562 human myeloid blast cells after treatment with increasing doses of STI571 using [1,2-13 C 2 ]glucose as the single tracer and biological mass spectrometry. In response to 0.68 and 6.8 M STI571, proliferation of Bcr-Abl-positive K562 cells showed a 57% and 74%… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
27
0

Year Published

2004
2004
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 171 publications
(28 citation statements)
references
References 29 publications
1
27
0
Order By: Relevance
“…LSCs have an increased oxygen consumption rate upon initial drug treatment [53]; however, our data suggest that with prolonged treatment, the more quiescent, TKI-persistent cells are biased towards glycolysis, possibly due to reduced energy requirements. Additionally, reductive carboxylation, a de novo lipogenesis pathway [69], and elongation of fatty acids in TKI-persistent K562 are consistent with utilization of carbon from glucose for nucleic acid and fatty acid synthesis [54,70]. Moreover, free fatty acids can form a feedforward loop with fatty acid oxidation, a reserve energy source [71].…”
Section: Discussionmentioning
confidence: 66%
See 1 more Smart Citation
“…LSCs have an increased oxygen consumption rate upon initial drug treatment [53]; however, our data suggest that with prolonged treatment, the more quiescent, TKI-persistent cells are biased towards glycolysis, possibly due to reduced energy requirements. Additionally, reductive carboxylation, a de novo lipogenesis pathway [69], and elongation of fatty acids in TKI-persistent K562 are consistent with utilization of carbon from glucose for nucleic acid and fatty acid synthesis [54,70]. Moreover, free fatty acids can form a feedforward loop with fatty acid oxidation, a reserve energy source [71].…”
Section: Discussionmentioning
confidence: 66%
“…CML stem and progenitor cells rely on oxidative phosphorylation compared to their non-transformed counterparts [44,53]. Moreover, short-term TKI-treatment of sensitive cells reduces glucose uptake and its utilization for nucleotide and fatty acid synthesis while increasing mitochondrial activity [54,55], but alterations in the metabolism of IM-persistent CML cells is yet to be studied. Thus, to examine metabolic differences between sensitive and IM-persistent K562, we measured cellular mitochondrial function and glycolysis using extracellular flux analyzer.…”
Section: Drug Insensitive CML Cells Have Altered Metabolism Mediated By Stat3mentioning
confidence: 99%
“…Recent studies analyzing glucose metabolic pathways using biological mass spectrometry have shown that several chemicals and natural products inhibit cell proliferation or tumor growth through regulation of glucose intermediate metabolism targeted at the oxidative PPP, the nonoxidative PPP, or both. 6,[11][12][13][14]20,21 The tyrosine kinase inhibitor genistein inhibits tumor growth primarily through the regulation of glucose metabolism, specifically targeting the nonoxidative PPP. 11 Avemar inhibits metastasis formation also primarily through the nonoxidative PPP, and it decreases activities of glucose-6-phosphate 1-dehydrogenase (G6PDH), a key enzyme in the oxidative PPP, as well as TK.…”
Section: Discussionmentioning
confidence: 99%
“…G6PDH and another key enzyme controlling oxidative reactions, hexokinase, are both inhibited by Gleevec treatment. 20 Methotrexate (MTX), currently in trials for colorectal carcinoma, inhibits the activity of G6PDH and 6-phosphogluconate dehydrogenases, both involved in oxidative PPP. 22 All these data suggest that inhibition of the glucose metabolism pathway may contribute significantly to the effects of cell proliferation and/or tumor growth inhibition and that inhibition of the glucose metabolism pathway may potentially be an effective way to treat cancer, a so-called "cancer starvation" strategy.…”
Section: Discussionmentioning
confidence: 99%
“…Imatinib mesylate, or Gleevec®, is a tyrosine kinase inhibitor that prevents the phosphorylation and activation of key enzymes in metabolic pathways (1). Specifically, Imatinib has been shown to reduce the activity of hexokinase, which is a key enzyme in the glycolysis pathway (3,18). Sindbis virus is dependent on glycolysis and it was predicted that inhibiting the glycolytic pathway would result in less viral replication.…”
mentioning
confidence: 99%